Athletics Formula 1 Games for Elementary School Students: Learning Achievement for 60 Meter Running Speed - Hadi, Syamsul; Hudain, Muh. Adnan; Kamaruddin, Ilham; Adil, Ahmad; Fahrizal, Fahrizal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to determine whether the implementation of the Kids Athletics Formula 1 game leads to an increase in 60-meter running speed among students in public elementary schools. The study also aims to develop innovative methods for enjoyable athletic learning for elementary school students. We conducted the study in two cycles using the Classroom Action Research method (planning, implementing actions, observation, and reflection). The subjects of the study were 18 grade VI students at public elementary school 7 Salatungo. The instrument used was a 60-meter running speed test with the Learning Objective Completion Criteria set at 80. The results of the study showed a significant increase in students' 60-meter running ability after the implementation of the Kids Athletics Formula 1 game. In the pre-cycle, the average student score was only 62 with a completion percentage of 0% (no students completed). In cycle I, the average score increased to 73 with a completion percentage of 22% (4 students completed). In cycle II, after the improvement of the learning method, the average score increased to 82 with a completion percentage of 100% (all 18 students completed the Learning Objective Achievement Criteria). The implementation of the Kids Athletics Formula 1 game has proven effective in increasing the 60-meter running speed of grade VI students at public elementary school 7 Salatungo. A fun learning approach through games can increase student enthusiasm and significantly improve their athletic skills.